A CONSTRUÇÃO DO SUJEITO EM SUA TRAJETÓRIA POLÍTICA: A IDENTIDADE DE UM CANDIDATO À PRESIDÊNCIA DA REPÚBLICA - Greco, Eliana Alves (Intercâmbio, 2010)
This article aims at verifying how the notions of both the discursive formation and inter-discourse contributed to the identities production in what concerns Lula’s speech during the elections in 1989 and 2002.